Menuju Kepemimpinan Pendidikan yang Efektif: Tantangan dan Strategi di Era Merdeka Belajar - Khairaningthias, Nur (Proceedings Series of Educational Studies, 2024)
Abstract In the era of Independent Learning, the challenges and strategies in achieving ef ective educational leadership are the primary focus in optimizing the quality of education in Indonesia. This research aims to analyze the dynamics of educational leadership amidst changes in the learning paradigm. Through a qualitative approach, this study conducted a literature review and in-depth interviews with educational stakeholders. The findings reveal that educational leaders need to pay attention to adapting to significant changes in education, such as the use of technology and innovation in teaching, as well as empowering teachers as change agents. Identified strategies include developing leadership competencies aligned with the new context, fostering collaboration among stakeholders, and implementing educational policies that support the principles of Independent Learning. This research highlights the importance of transformation in the mindset and practices of educational leadership to support the realization of the Independent Learning vision within the Indonesian education system.